Mathematical Challenges in Biology: Identifying Core Learning Difficulties - Harini, Novita Vindri (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Biology students often face difficulties in understanding basic mathematical concepts, which can impact their comprehension of advanced science courses. This study aims to identify the key mathematical topics that pose challenges for first-year biology students to facilitate instructional improvements before the final exam. The research involved an analysis of midterm exam results from 90 students enrolled in a Basic Mathematics course. The data examined included completion time and accuracy rates across six key topics: equations and inequalities, matrices, absolute value, real numbers, probability, and sets. The results indicated that probability had the longest average completion time (4 minutes 36 seconds), while absolute value had the highest error rate, with only 13.19% correct responses. Further interviews revealed that students struggled with understanding the formal concept of absolute value and often misapplied probability rules for independent events. These findings highlight the need for improved teaching strategies, particularly for topics with high error rates, such as concept-based approaches and more structured problem-solving exercises. Enhancing students' mathematical proficiency through targeted interventions is expected to better prepare them for future academic challenges.